Telaah Kritis Kebijakan Tol Laut Pada Periode Kedua Presiden Joko Widodo - Muhammad Asy Ari Badar; Agus Salim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Maritime Highway Policy, as an effort by the Indonesian government to strengthen maritime connectivity and support economic growth, has become the main focus during the second term of President Joko Widodo's leadership. This research evaluates the concept, implementation and impact of this policy in the development of the maritime sector and national economy. The research results show that the Maritime Highway Policy has succeeded in increasing connectivity between regions, leveling economic growth, increasing investment, and supporting the revitalization of the maritime sector. With these efforts, Indonesia is further strengthening its image as a strong and competitive maritime country. This research provides insight into the important role of the Maritime Highway Policy in developing Indonesia's maritime economy and connectivity, supporting sustainable development, and reducing economic disparities between regions.